2000
DOI: 10.1111/j.1095-8649.2000.tb00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress responses to confinement in diploid and triploid Atlantic salmon

Abstract: Confinement of juvenile Atlantic salmon Salmo salar from four different populations (allfemale diploids, all-female triploids, mixed sex diploids and mixed sex triploids) either before (FW parr) or after (SW smolts) transfer to sea elevated plasma cortisol and plasma lactate from control levels irrespective of ploidy status. Both before and after confinement, plasma cortisol levels in SW smolts (6-174 ng ml 1 ) were higher than those in FW parr (4-58 ng ml 1 ), which possibly reflected the physiological challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 48 publications
5
25
1
Order By: Relevance
“…Somatic growth continues in triploids and flesh quality is maintained over the period when diploid fish are sexually maturing and undergoing associated reduction in flesh quality (Sadler et al 2000). However, despite the obvious advantages of using triploids, there are a number of problems associated with the commercial production of all-female triploid fish.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic growth continues in triploids and flesh quality is maintained over the period when diploid fish are sexually maturing and undergoing associated reduction in flesh quality (Sadler et al 2000). However, despite the obvious advantages of using triploids, there are a number of problems associated with the commercial production of all-female triploid fish.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, likely that bathing is less effective in smaller size cages. This could be due to a range of factors such as confinement stress (Sadler et al 2000), dominant behaviour (MacClean & Metcalfe 2001) and inability for escapement possibly leading to an increased chance of AGD-affected fish infecting unaffected fish.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was a 13-fold increased likelihood of infection with Kudoa thyrsites for sexually mature salmon compared to sexually immature salmon (StHilaire et al 1998). Also, higher cortisol levels, a measure for primary stress responses (Sadler et al 2000), were found in mixed sex populations compared to allfemale populations. High cortisol levels have also been associated with immunosuppression (Bakke & Harris 1998, Sadler et al 2000.…”
mentioning
confidence: 90%
See 2 more Smart Citations